Metodologia de projetos no ensino de Biologia: identificação e proposição de soluções para mitigar algumas questões ambientais de uma comunidade - Patrícia Mara Silva Gonçalves (2020)
In the last decades there has been a great discussion about the teaching methods commonly used in public schools. The so-called traditional educational methodologies, which prioritize memorization, where the teacher has a role of transmitting information, have not kept up with the demands of modern society and, therefore, it is necessary to adopt more inclusive strategies, in which students have an active participation in the construction of knowledge. One, among so many possibilities, is the use of Project Methodology, an investigative teaching model that enhances the role of students, promotes meaningful learning and contributes to the process of scientific literacy. In this context, this work is a qualitative research, developed through meetings on the school shift and in the out-of-school shift with high school students from a public school in Minas Gerais, whose objective was to identify environmental issues in the community and, through development of projects, create proposals to mitigate them. The central theme, waste management, was chosen by students who, set in teams, developed projects with the teacher's guidance on the sub-themes: work at the waste sorting and composting plant, plastic recycling, paper and waste recycling at school and domestic waste burning. The activities were varied, carried out collectively, emphasizing the practice of technical visits with interviews, scientific report writing and results presentation during the science fair. Besides these ones, the groups developed specific actions such as the preparation of an information pamphlet, the preparation of models and dynamics, workshops and the creation of prototypes and alternative products. The evaluation was made during the whole process with observation and recording in a field notebook, and at the end of the work, through a conversation with each group and a narrative carried out individually. In view of the various stages of the research, students behaved in a variable way, showing, in most cases, interest, satisfaction and motivation, but there were also moments of doubts, frustrations and complaints. Even so, it was possible to perceive the appropriation of knowledge in writing, in speech and even in the students' attitudes. Although they had difficulty in writing, the students developed well-structured works, with good reasoning and creativity, considering the scientific language. They also interacted with visitors during the presentations at the science fair, an opportunity in which they demonstrated the importance of the work done at the plant and encouraged participation in selective collection. Thus, doing this work provided students with the experience of a new way of learning, in which they investigated and actively participated in the entire learning process, with a positive response. In addition, the use of this teaching methodology contributed to the process of scientific literacy of these students, helping critical development in recognizing the importance of their actions in the community, thus allowing citizenship awareness.